Internalisasi Nilai Moderasi Beragama dalam Pendidikan Islam: Studi Kepustakaan pada Madrasah, Pesantren, dan PTKIN - Mhd. Rizkiy Bahar Siregar; Lahmuddin Lubis (Medan Resource Center, 2025)
This article examines Islamic education and religious moderation as a strategic paradigm for shaping students who are faithful, tolerant, and capable of living harmoniously in plural societies. In recent years, rising religious polarization and exclusivist interpretations have intensified academic debates on the role of education in preventing radical tendencies and strengthening social cohesion. Within this context, Islamic education is expected not only to transmit religious knowledge but also to cultivate ethical awareness, justice, and balance (wasathiyah) as foundational values. The study aims to (1) analyze the conceptual foundations of religious moderation within Islamic educational thought and (2) examine its implementation in Islamic educational institutions, including madrasahs, pesantren, and Islamic higher education institutions. This article employs a qualitative literature review approach by critically analyzing relevant books and peer-reviewed scholarly works. The findings indicate that religious moderation constitutes an intrinsic normative-epistemological principle of Islamic education, rooted in the Qur’anic concept of wasathiyah, and functions as a framework for integrating faith, rationality, and social responsibility. Its effective implementation requires systemic integration into curriculum design, pedagogical strategies, institutional culture, and educational policy. The study argues that consistent institutionalization of religious moderation strengthens inclusive religious attitudes, civic commitment, and ethical conduct among students. Theoretically, this study reinforces the position of wasathiyah as a foundational paradigm in contemporary Islamic educational discourse. Practically, it provides a conceptual basis for policymakers and educators to mainstream moderation values in institutional governance and instructional practice.